SECONDARY INCOME ENTRY AS ONE OF THE FINANCING INSTRUMENTS OF FOREIGN TRADE DEFICIT: SAMPLE OF TURKEY - Sinem YAPAR SAÇIK (Fırat University, 2019)
Balance of payments which economic transactions registered among all residents of a country with all residents of other countries is the most important indicator in terms of a country’s financial credit. Besides the credit of the country, balance of payments have great importance for all countries due to exposing foreign balance and results of macroeconomic policies imposed. Because of this importance the balance of payments issue finds wide position in economics literature in terms of topics such as foreign balance policies, sustainability and financing of current deficit and economic effects of major account entries. Current account is the most major account group of balance of payments which have four major account group namely current, capital, finance and net errors and omissions. Current account is constituted by other sub-accounts namely merchandise trade, service trade, primary income and secondary income. One of the properties of balance of payments is that a monetary payment is accrued generally in response to every economic transaction. Other economic transactions which are exceptional regarding the previous statement are recorded to secondary income entry. This entry is generally considered as insignificant due to its exceptional feature and cannot find a place for itself in economic literature. In this study which is prepared to fill this blank, financing effect/ineffectiveness of secondary income entry in Turkey’s foreign trade deficit is analyzed. Analyzing data for 1984-2014 years; it is concluded that secondary income entry is effective in periods when Turkey’s openness ratio is low and inefficient in periods when the same ratio is high.